Sacrifice Ratios and Inflation Targeting: The Role of Credibility (2012)
Two recent papers (Gonçalves and Carvalho, 2009; and Brito, 2010) hold contradictory views regarding the role of inflation targeting during periods of disinflation. The first paper claims that inflation targeting reduces sacrifice ratios¿i.e., the ratio of output losses to the change in trend inflation¿during disinflations; the second paper refutes this result. We show here that inflation targeting only matters if disinflations are slow. The credibility gains of a fast disinflation make inflation targeting irrelevant for reducing the output-inflation trade-off.